ความพึงพอใจของประชาชนต่อการให้บริการด้านงานทะเบียนและบัตร เทศบาลตำบลบ้านเป็ด อำเภอเมืองขอนแก่น จังหวัดขอนแก่น - และคณะ, พระมหาวิไลศักดิ์ ปญฺญาวโร, ดร. (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2019)
The research has the aims to study: 1) the satisfaction of the people to card and registration services of Ban Pet Municipal sub - district, Muang Khonkaen district, Khonkaen province. The researcher collected the data from 396 sampling respondents by questionnaires, and analyzed the data by percentage, mean, and standard deviation statistics. The results were as follows: Most of the respondents, 54.44 percent, were female, and 45.45 percent were male. The respondents, 29.80 percent, were age above 31 years old, 20.96 percent were 16-20 years old, 19.70 percent were 26-30 years old, 18.18 percent were 21-25 years old, and 11.36 percent were 15 years old. Most of the respondents, 26.77 percent, were graduated higher secondary school, 23.99 percent were graduated secondary school, 23.23 percent were graduated diploma, 18.43 percent were graduated primary school, and 7.58 percent were graduated higher than bachelor degree. Lot of the respondents, 27.53 percent, were students, 19.95 percent were labours, 18.43 percent were merchants, 12.63 percent were state servants and state enterprise, 11.87 percent were farmer, and 9.60 percent of the respondents were freelance. The overall people’s opinion to card and registration services of Ban Pet Municipal sub-district, Muang Khonkaen district, Khonkaen province was at high mean level(=4.34), the aspect of officers(=3.78), the aspect of building(=3.49), the aspect of fast service(=3.55), the aspect of equal service( = 3.64), the aspect of public relation(= 3.71) and thePublic relations (= 3.52) There were 4 suggestion from this study: 1) the officers should add numbers of officers in the municipality to serve the people, 2) the municipality should provide the space for car parking, sufficient toilets, and chairs, 3) the officers should quickly serve the people, and 4) the municipality should use modern technology to inform the people. Keywords: People’s satisfaction, The service